If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 48 = 5 Reorder the terms: 48 + 3x = 5 Solving 48 + 3x = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-48' to each side of the equation. 48 + -48 + 3x = 5 + -48 Combine like terms: 48 + -48 = 0 0 + 3x = 5 + -48 3x = 5 + -48 Combine like terms: 5 + -48 = -43 3x = -43 Divide each side by '3'. x = -14.33333333 Simplifying x = -14.33333333
| -2+10+4= | | 3(t+6)= | | -45y=-90 | | 4-6b=40 | | -457=-90 | | 4x-10=7x-16 | | 2(150-0.5y)+y=300 | | -14=-7v | | 6a-9=3a+6 | | 80-(4x+15)=4(x+5)+x | | (2x-4)+9i=8+3i | | -32=3+9(f+5) | | 2y-2y=14+4y | | 4t-4=2t-2 | | 3a-12=6a-21 | | 8k+8(k-1)=5k+36 | | 13x-7x-35=6x-35 | | 2a+14=5a+5 | | Y=x^2-9x+8 | | 2g+14+5g-8g=3+8 | | 6t+12=18 | | 7(1-3n)-2n=-85 | | 5y^2-12y+5=0 | | 2g+14+5g-8g=3-8 | | (6x+2)(x-3)=0 | | 3w-8=7w | | y=0.5+b | | 2*x^3-3*x^2-72*x+3=0 | | 7p+4=67 | | 6r+9=63 | | t^2(t^2-5)=2t^2-5 | | 6x+1y=30 |